Vibration of the system with nonlinear springs connected in series - Awrejcewicz, Jan; Starosta, Roman; Sypniewska-Kamińska, Grażyna (Wydawnictwo Politechniki Łódzkiej, 2021)
Solution of the problem and qualitative analysis of the forced vibration of the spring pendulum containing nonlinear springs connected in series is made in the paper. The method of multiple scales in time domain (MMS) has been employed in order to carry out the analytical computations. The MMS allows one, among others, to predict the resonances which can appear in the systems. The approximate solution of analytical form has been obtained for vibration at main resonance.
Keywords: asymptotic analysis; multiple scales; differential-algebraic system; springs in series; analiza asymptotyczna; skale wielokrotne; system różniczkowo-algebraiczny; sprężyny szeregowe